Kebijakan Medik pada Pasien Gagal Ginjal Kronik dengan Hemodialisis di RS Hasan Sadikin Bandung - Dewi Marhaeni Diah Herawati; Eko Fuji Ariyanto (Center for Health Policy and Management, 2014)
Background: Prevalence of Chronic Kidney Disease in dialysis’s patients in Indonesia has increased. Some of them occurred with malnutrition inflammation complex syndrome and lead to death. This study aims to determine the intake of protein and energy, and determine factors that cause the low intake of nutrition. Methods: Design of the study was mixed methods using embedded concurrent strategy. Research paradigm was constructivism whereas qualitative research conducted in-depth interviews and observations. Quantitative research has been done with a descriptive approach, observational, using secondary data and perform 24 Hour Recall and Food Frequency Questionnaire (FFQ). The study was conducted at Hemodialysis Unit, Hasan Sadikin Hospital from June to September 2013, with a total sampling. Qualitative and quantitative data analysis has been done, followed by analysis of policy and analysis for policy for establishing a medical policy for chronic kidney disease patients receiving medical hemodialysis. Result: The average protein intake of the patients was 1.32 g/ kg/day. Interval of protein intake of 0.5 g/kg /day (lowest) until 2.8 g/kg/day (highest). 24% of patients had protein intake under 1 g /kg BW/day and 22.8% was above 1.5 g/kg BW/day. Average energy intake was 2001 kcal patient/day (930 kcal/ day - 3196.9 kcal/day). The qualitative analysis resulted in seven themes which causes nutrient low intake. The themes were underlying diseases (such as diabetes mellitus and hypertension), length of dialysis, frequency and number of dialysis, effects of dialysis, body’s response, cost factor, counseling, and education. Most of the respondents felt suffer from anemia and complained of nausea and vomiting. Body responses varied widely among them. Conclusion: Protein intake of dialysis patients as recommended by K/DOQI, but not in accordance with energy intake. Protein and energy intake of Jakeman's holder patients were lower than the recommendation of K/DOQI. The cause of lower intake of nutrients due to the underlying disease, length of dialysis, frequency and number of dialysis, effects of dialysis, body responses, cost factors and lack of counseling and education. Counseling and education of the patient's hospital are needed. The government should encourage medical policy in the management of patients with chronic kidney failure are comprehensive, in primary care, secondary and tertiary. The government must provide competent personnel, facilities and supporting infrastructure, service standards and standard operating procedures are required for each level of service. Latar Belakang: Prevalensi pasien Penyakit Ginjal Kronik (PGK) yang menjalani hemodialisis di Indonesia mengalami peningkatan. Beberapa diantaranya terjadi malnutrition inflammation complex syndrome dan berujung pada kematian. Penelitian bertujuan untuk mengetahui asupan protein dan energi, serta mengetahui faktor-faktor yang menyebabkan rendahnya asupan nutrisi. Metode: Desain penelitian adalah mixed method dengan menggunakan strategi conccurent embedded. Paradigma penelitian adalah constructivisme. Penelitian kuantitatif dengan pendekatan deskriptif, observational menggunakan data skunder dan melakukan 24 Hour Recall dan Food Frequency Questionaire (FFQ). Penelitian kualitatif dilakukan dengan wawancara mendalam dan observasi. Penelitian dilakukan di Unit Hemodialisis Rumah Sakit Hasan Sadikin Bandung bulan Juni-September 2013 dengan total sampling. Dilakukan analisis data kualitatif dan kuantitatif yang diikuti analysis of policy dan analysis for policy untuk merumuskan kebijakan medik pada pasien PGK yang menjalani hemodialisis. Hasil: Rata-rata asupan protein pasien adalah 1,32 gr/kg BB/ Hari. Asupan protein terendah 0,5 gr/kg BB/hari, tertinggi 2,8 gr/kg BB/hari. Asupan protein pada 24% pasien dibawah 1 gr/ kg BB/hari; 22,8% diatas 1,5 gr/kg BB/hari. Rata-rata asupan energi pasien 2001 kkal/hari, asupan terendah 930 kkal/hari, tertinggi 3196,9 kkal/hari. Analisis kualitatif menghasilkan 7 tema yang menjadi penyebab rendahnya asupan nutrisi yaitu penyakit dasar (diabetes mellitus, hipertensi), lama dialisis, frekuensi dan jumlah dialisis, efek dialisis, respon tubuh, faktor biaya dan konseling serta edukasi. Efek dialisis yang paling dikeluhkan adalah anemia, mual dan muntah. Respon tubuh diantara pasien sangat bervariasi. Konseling dan edukasi dari pihak rumah sakit sangat dibutuhkan pasien. Kesimpulan: Asupan protein pasien sesuai rekomendasi K/ DOQI, namun belum sesuai untuk asupan energi. Asupan protein dan energi pasien Jamkesmas lebih rendah dari rekomendasi K/DOQI. Penyebab rendahnya asupan nutrisi disebabkan karena penyakit dasar yang menjadi penyebab PGK, lama dialisis, frekuensi dan jumlah dialisis, efek dialisis, respon tubuh, faktor biaya dan tidak adanya konseling dan edukasi. Pemerintah harus mendorong kebijakan medik dalam penanganan pasien gagal ginjal kronik yang komprehensif, di pelayanan primer, skunder dan tertier. Untuk tercapainya kebijakan medik tersebut pemerintah harus menyediakan tenaga yang kompeten, sarana dan prasarana pendukung, standar dan protap yang dibutuhkan untuk masing-masing level pelayanan.